A comparison of untreated and formaldehyde-treated barley distiller's solubles and rapeseed meal as protein supplements in dairy cows given grass silage ad libitum - Huhtanen, P.; Khalili, H.; Nasi, M. (1991)
In a 4 X 4 Latin square design trial with 4-week periods, 20 Friesian cows with average milk yield 28.4 kg were given a diet of grass silage ad libitum plus concentrates based on barley, oats and barley fibre (250, 250 and 500 g/kg) at 8.5 kg/day (control) or with rapeseed oilmeal, dried distillers' solubles (DDS) or formaldehyde treated (15 litre/tonne) DDS (TDDS) replacing 1.5 kg/day of basal concentrate. Protein supplementation increased silage and total DM intake by about 0.5 kg/day (P 0.05). Milk yield (P 0.1), protein content (P 0.05) and protein yield (P 0.01) were increased. Untreated DDS had no effect on milk yield or milk composition compared with the control diet. Treatment of TDDS increased milk and protein yield compared with DDS, and milk yields were similar to that obtained with rapeseed meal. Compared with rapeseed meal, the meal milk protein yield was lower (P 0.01) when the diet was supplemented with DDS. Liveweight gain was higher (P 0.05) in cows fed on rapeseed meal diet than in cows fed on DDS. Calculation of energy balance showed that increased milk energy output in cows fed on diets containing protein supplements was mediated mainly through increased energy intake.